Socialization of Financial Literacy the Importance of Recording and Preparation Financial Reports in Hulu Madras Sub-District Medan City - Richna Handriyani; Rifqah Harahap; Siti Junaidah Hasibuan; Raymond Fransiscus (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Financial literacy is closely related to individual welfare. Financial knowledge and skills in managing personal finances are very important in everyday life. financial gain is not only a function of income alone (decrease in income). This community service aims to provide socialization of the importance of recording and preparing financial reports at the Hulu Medan Lurah Madras Office. The method used in data collection is the method of observation and community service activities. In its implementation, the method of discussion and lecture material is used. The results obtained from this community service are the increased knowledge and understanding of the participants regarding the importance of recording and preparing financial reports.